Insertion of adenovirus type 12 DNA in the vicinity of an intracisternal A particle genome in Syrian hamster tumor cells. - Lichtenberg, U (1987)
In the adenovirus type 12 (Ad12)-induced hamster tumor T1111(2) about 10 Ad12 genome equivalents were integrated at different sites. One of the integrated copies proved unstable and was lost from the cellular genome or rearranged upon passage of the cell line, H1111(2), established from this tumor. This unstable site of junction between the left terminus of Ad12 DNA and hamster DNA and the preinsertion site from BHK21 hamster cells was cloned, sequenced, and analyzed. The junction site showed several peculiarities. At the left terminus of Ad12 DNA, the first 64 nucleotides were deleted. At a distance of 127 nucleotides to the left from this junction site, an internal dispersed fragment of Ad12 DNA comprising nucleotides 1290 to 1361 of the authentic Ad12 DNA sequence was inserted into cellular DNA in an inverted orientation relative to the complete Ad12 genome that was located in its vicinity. The 127-nucleotide sequence between the intact Ad12 genome and the separate 72-base-pair (bp) Ad12 DNA fragment was cellular, but it was not identical to the preinsertion sequence at this location. The sequences flanking the termini of the dispersed 72-bp Ad12 DNA fragment were characterized by direct repeats of 9 or 10 nucleotides. To the left of Ad12 nucleotide 1361 in the separate 72-bp fragment, about 620 cellular nucleotides followed which were identical at the occupied and at the preinsertion sites. It was conceivable that the separate 72-bp Ad12 DNA fragment and the cellular sequence of 127 bp to its right had been transposed en bloc from another unknown location. Abutting the 620 nucleotides of cellular DNA to the left of this block, the 3'-terminal sequence of an endogenous, intracisternal A particle (IAP) genome of hamster cells was detected. The possible significance of the proximity of an IAP sequence to an inserted Ad12 genome with respect to the transformation event, to the instability at this site, or to the transcriptional activity of this region is not known. The 620 bp of cellular DNA between the 72-bp Ad12 DNA fragment and the end of the long terminal repeat of the hamster IAP sequence was apparently of a unique type. Transcriptional activity was not found in the approximate region between nucleotides -620 (to the left) and +350 (to the right) relative to the site of Ad12 DNA insertion, but was found outside these boundaries.